Transcultural psychotherapy and positive psichology: an integrated model - E. F. M. Riva (2008)
This intervention aims to expose a clinical approach that melts theories and practices taken from transcultural psychology and psychotherapy and theories and instruments coming from the field of positive psychology. Among the clinicians of transcultural psychology we refer in particular to the psychodynamic ones of the French school, as Nathan, Fleury, Sironi, Moro, and to the Italian school (Terranova-Cecchini, Losi, Inglese, Beneduce). Among the authors of Positive Psychology we refer in particular to Csikszentmihalyi (Csikszentmihalyi e Schneider 2000; Csikszentmihalyi 1990; Csikszentmihalyi e Csikszentmihalyi Selega 1988), Seligman (Peterson e Seligman 2004) and Inghilleri (2002). Starting from clinical cases, both of omocultural (Italian patient and Italian clinician) and transcultural (Italian patient and foreign clinician) situations, and using qualitative and descriptive methods, it will be shown how to conjugate the theoretical and technical properties of both research fields in a more complex and individually-adapted clinical model. Some clinical results will be exposed.